Identification of a mouse TBP-like protein (TLP) distantly related to the drosophila TBP-related factor. - Ohbayashi, T (1999)
TATA-binding protein (TBP) is an essential factor for eukaryotic transcription. In this study, we demonstrated a mouse cDNA encoding a 21 kDa TBP-like protein (TLP). The TLP ORF, carrying 186 amino acids, covered the entire 180 amino acids of the C-terminal conserved domain of mouse TBP with 39% identity and 76% similarity. Northern blot analysis demonstrated that TLP mRNAs were expressed in various mammalian tissues ubiquitously and that their distribution pattern was analogous to that of TBP. By using anti-TLP antibody, we demonstrated the existence of TLP proteins in various mammalian cells and tissues. The Drosophila TBP-related factor (TRF) is a neurogenesis-related transcription factor that binds to the TATA-box and activates transcription. TLP did not bind to the TATA-box nor direct transcription initiation. Multiple amino acids critical for TBP function were deleted or substituted in TLP, while amino acids in Drosophila TRF much resembled those in TBP. Similarity between Drosophila TRF and mouse TLP was considerably lower (alignment score 35) than that between Drosophila TBP and mouse TBP (alignment score 88). Identity of nucleotide sequences between mouse and putative human TLPs (94%) was higher than that between TBPs (91%) in these two animals. Expression of TLP was nearly constant throughout the P19 differentiation process. Accordingly, we suggest that, even if higher eukaryotes generally contain multiple tbp -related genes, TLP is not a bona fide mammalian counterpart of Drosophila TRF.